Extended Gergonne syllogisms - Johnson, Fred (Frederick A.), author; Kluwer Academic Publishers, publisher (Colorado State University. Libraries, 1997)
Syllogisms with or without negative terms are studied by using Gergonne's ideas. Soundness, completeness, and decidability results are given.
Keywords: negative; logic; language; syllogism